2001
DOI: 10.1590/s0102-311x2001000500024
|View full text |Cite
|
Sign up to set email alerts
|

Diferenças no padrão de ocorrência da mortalidade neonatal e pós-neonatal no Município de Goiânia, Brasil, 1992-1996: análise espacial para identificação das áreas de risco

Abstract: Este artigo refere-se à pesquisa acerca do padrão espacial dos componentes neonatal e pós-neonatal da mortalidade infantil em Goiânia, no Estado de Goiás, Brasil. A população do estudo foi a coorte de 101 mil nascidos vivos, residentes em Goiânia, de 1992 a 1996. As probabilidades de morte infantil foram estimadas mediante o cotejo dos arquivos de óbitos e de nascidos vivos. Para minimizar as flutuações aleatórias das taxas, empregou-se o método Bayesiano empírico. A unidade de análise do padrão espacial foi c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
4

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 12 publications
0
8
0
4
Order By: Relevance
“…Morais-Neto et al 34 , estudando a relação entre o processo de urbanização de Goiânia, constataram que a rápida e desordenada formação das periferias das grandes metrópoles vem criando bolsões de carência social e de exclusão de atendimento em saúde, exigindo novas estraté-gias de controle das endemias.…”
Section: Resultsunclassified
“…Morais-Neto et al 34 , estudando a relação entre o processo de urbanização de Goiânia, constataram que a rápida e desordenada formação das periferias das grandes metrópoles vem criando bolsões de carência social e de exclusão de atendimento em saúde, exigindo novas estraté-gias de controle das endemias.…”
Section: Resultsunclassified
“…In the city of Goiânia, Brazil, Morais-Neto et al (7) used spatial analysis to evaluate risk areas for neonatal death and drew attention to the importance of their study in the development of possible health care actions; Nascimento et al (8) in a study about the same topic in the Paraíba Valley found spatial clusters of neonatal mortality and identified the need of municipal interventions.…”
Section: Introductionmentioning
confidence: 99%
“…(Câmara et al, 2002;Tavares, 2006). In the study of the geographical distribution of a disease, it is either possible to carry out an exploratory analysis with the objective to describe and explain how the disease appears from a purely spatial viewpoint or, alternatively, to examine if there exists a spatial dependence of the standard distribution (Hills and Alexander, 1989;Marshall, 1991;Bailey and Gatrell, 1995;Lawson and Kulldorff, 1999;Morais-Neto et al, 2001). This type of precise information in relation to the casual characteristics of determined events makes it possible for health agencies to produce better and more selective policies for intervention and control (Costa et al, 2006).…”
Section: Introductionmentioning
confidence: 99%